PELATIHAN PEMBUATAN PETA DESA MENGGUNAKAN APLIKASI GIS DI KECAMATAN SAHU KABUPATEN HALMAHERA BARAT - Musdar Muhammad; Ruliyanto Syahrain (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
The availability of village maps contained in the village, Tacim, Susupu village, Ropu Tengah Balu village, Lako Akelamo village and Lako Akediri village that are valid and reliable is the forerunner of the determination of village boundaries at the level above it, and is a fundamental database in realizing village development goals. The purpose of devotion; providing understanding and training to the village government, the importance of village maps, for making village policies and planning by looking at data or maps for the progress of the village. The method of implementing pkm activities using the method of work / art methhods is a method that can be used for the benefit of the community and uses the Method of Focus Group Discussion (FGD) and Training. The results of the service were carried out on May 21, 2022, located in the village of Ropu Tengah Balu. This activity was held on Saturday at 20.00. until it was completed, there were 30 participants. To advance the village, it is necessary to increase the capacity of the village government, so that there are adequate human resources to promote the village, the village government through the village kepala must conduct trainings to village officials, to the community and youth shops.